Appraisal of surface preparation in adhesive bonding of additive manufactured substrates. (April 2021) - Frascio, M.; Mandolfino, C.; Moroni, F.; Jilich, M.; Lagazzo, A.; Pizzorni, M.; Bergonzi, L.; Morano, C.; Alfano, M.; Avalle, M.
Abstract: This work emphasizes the critical need of surface preparation to improve the performance of adhesively bonded 3D printed Acrylonitrile Butadiene Styrene (ABS) adherends obtained using Fused Filament Fabrication (FFF). In particular, mechanical abrasion and two different plasma pre-treatments, i.e., Atmospheric Pressure Plasma (APP) and Low-Pressure Plasma (LPP), were compared through the qualitative analysis of surface wettability, using static and dynamic contact angle measurements, and the quantitative evaluation of surface roughness measured using optical profilometry. In addition, mechanical tests were carried out using the single lap joint configuration and the interaction between the treated ABS substrates and three different adhesive materials, epoxy, polyurethane and modified silane, were carefully ascertained. The results indicated that the plasma process at low pressure (LPP) enabled a substantial decrease of contact angle (θ < 10 o ), with little modifications of surface morphology and topography with respect to the reference solvent cleaned surface (θ > 80 o ). The improved wetting was accompanied by a relevant increase in the joint strength. The actual mechanism of fracture shifted from adhesive failure, typical of solvent cleaned and abraded surfaces, to full cohesive failure within either the substrates of the adhesive layer. Besides, a strong influence of the adhesive selected for manufacturing was reported. Indeed, using a tough bi-component epoxy adhesive in conjunction with the LPP pre-treatment led to substrate failure, representing the largest possible enhancement of joint strength. The shear strength was over 300% of that obtained with reference solvent cleaned, and 80% larger than that recorded on abraded surfaces.